Study of soil management in rice fields in Bantimurung District Maros Regency. Issue 4 (July 2021) - Safitri, D E; Ahmad, A; Nathan, M
Abstract: Rice productivity in Bantimurung District is unstable every year. Farmers tend not to attend to environmental and soil protection but are racing to increase yields rapidly using excessive chemical fertilizers and pesticides, tilling the soil too frequently, and burning postharvest straw. This study aims to study rice fields' management in Bantimurung District, Maros Regency, based on the soil's physical and chemical characteristics, which are expected to be a source of information in managing rice fields in Bantimurung District, Maros Regency. Data were collected using a field survey method in irrigated and rainfed rice fields and farmer interviews. Laboratory analysis included soil texture, bulk density, N-total, C-organic, pH, and organic functional group analysis. The result showed that both irrigated and rainfed rice fields have the low category of N-total (0.1-0.23%), low to a moderate category of c-organic (1.87-3.16%), and slightly acid to neutral pH (5.98-6.67). Based on farmers' information, we know that the rice fields in Bantimurung District are still suitable for rice production but must have a proper good management principle. The best management includes not using an-organic fertilizer excessively, adding organic matter, crop rotation, and attending to water needs.